Focusing oriented art therapy as a means of stress reduction to students at UiTM Melaka city campus / Siti Norah Mohd Sarmin - Mohd Sarmin, Siti Norah (Faculty of Art and Design, 2015)
This study sought to test the effectiveness of using a mindfulness based practice, Focusing-Oriented Art Therapy, as a way to reduce stress and raise students' perceived levels of self-compassion as a student. Participants consisted of 5 students from UiTM Melaka City Campus. This thesis using a qualitative techniques to know how effectiveness of using Art therapy as a way to reduce their stress. Stress is a strain or tension tension that is either physical, mental, or emotional. Art therapy is a form of expressive therapy that uses the creative process of making art improve a person's physical, mental and emotional well being. Individuals who benefits from art therapy include those who have survived trauma resulting from combat, abuse, traumatic brain injury and other health. Art therapy help people resolve conflicts, improve interpersonal skills, manage problematic behaviours, reduce negative stress and achieve personal insight. From this thesis, I will using a quantitative and qualitative for methodology to find the result. Quantitative will find the result about what percentage of stress level that participate. For the qualitative survey, I using a activity and ask that participate about art therapy. This method result will find the effectiveness of using art therapy technique.